ENHANCED ANTICONVULSANT EFFICACY OF INTERLEUKIN RECEPTOR BLOCKADE FOLLOWING LEVETIRACETAM USE - Vastyanov, R.S.; Krepec, Yu.S.; Stoyanov, O.M.; Dobrovolskyi, V.V.; Stepanov, G.F.; Savytskyi, I.V.; Kalashnikov, V.Y. (World of Medicine and Biology, 2025)
The purpose of the study was to determine the principal possibility of enhancement of the anticonvulsant effect of interleukin receptor blockade by levetiracetam in chronic experimental epileptogenesis. Experimental studies were performed on models of acute generalized and chronic epileptic activity. Rats were treated with systemic and intracerebroventricular injections of a recombinant interleukin receptor blocker, administered in combination with levetiracetam. Interleukin receptor activity block was shown to protect animals from acute generalized and chronic seizures during kindling and postkindling. The revealed recombinant interleukin receptor antagonist, when administered systemically and intracerebroventricularly, shows anticonvulsant efficacy that is enhanced by levetiracetam. The revealed anticonvulsant effect is observed in acute generalized pentylenetetrazole- and kainic acid-induced seizures, as well as in a chronic convulsive syndrome under intra-hippocampal blockade of interleukin receptors. The obtained results indicate that the inflammatory response is involved in the pathogenetic mechanisms of seizure syndrome. The author concludes that the fundamental possibility of increasing anticonvulsant therapy efficacy in patients with refractory epilepsy was achieved through the co-administration of drugs that block neurotransmitter systems responsible for the initiation and propagation of excessive bioelectrical activity.
Keywords: convulsive syndrome; kindling; postkindling; cytokines; recombinant antagonist of interleukin-1 receptors; levetiracetam; neurotransmitter systems; pathogenetic mechanisms